Human influenza virus hemagglutinin is expressed in monkey cells using simian virus 40 vectors. - Hartman, J R (1982)
We have cloned and expressed the hemagglutinin (HA) gene of a human influenza virus (A/WSN/33) in monkey kidney cells by linking it to deleted simian virus 40 (SV40) genomes that contain the entire early gene region, the origin of replication, and late leader sequences. The HA gene (1775 base pairs long) was originally inserted by the dG . dC tailing technique into the multicopy plasmid of Escherichia coli, pBR322, using cDNA made from viral RNA. The cloned gene was further modified by treatment with nuclease Bal 31 to remove the dG . dC tails and some of the untranslated sequences and recloned in E. coli after addition of BamHI restriction endonuclease linkers. A number of SV40 and HA recombinants (SV--HA) were constructed by inserting recloned HA DNA into the late gene region of SV40. The SV--HA recombinants, when complemented in a lytic infection of monkey cells by the helper function of SV40 early deletion mutants expressed influenza HA as detected by immunofluorescence and immunoprecipitation of in vivo-labeled proteins using either heterogeneous anti-influenza rabbit antibodies or monoclonal antibodies against HA. Furthermore, the WSN HA expressed by the SV--HA recombinants was also glycosylated and possessed the same molecular weight (approximately 70,000) as the uncleaved HA of WSN virus in monkey cells.